The importance of Icelandic riverplains as breeding habitats for Whimbrels Numenius phaeopus - Borgný Katrínardóttir 1980- (2012)
Capsule: Threatened riverplain habitats in Iceland, which hold a substantial proportion of the world population of Whimbrels, had much higher breeding densities than other habitats but proportion of successful breeders was similar between habitats. Aim: To estimate the conservation value of preferred breeding habitats of Whimbrels through comparison with other breeding habitats at different spatial scales. Results: Whimbrels breed consistently at much higher densities in the preferred riverplain habitats than in other habitats frequently used by the species in Iceland. Breeding output measured as the proportion of breeding pairs with chicks did however not differ significantly. Comparison of resource abundance between riverplain and other habitats was not conclusive, possibly due to two volcanic eruptions which may have affected invertebrate abundance in the study areas. We estimate that c. 22% of the Icelandic population of Whimbrels and c. 10% of the world population of the species breed in riverplains in Iceland. Conclusion: The study shows that the threatened riverplain habitat in Iceland is an important breeding ground for Whimbrels but further work is needed to elucidate the drivers of habitat preferences. University of Iceland Research Fund Icelandic Research Fund for Graduate Students Natturuverndarsjodur Palma Jonssonar.